Uzbekistan's strategic reliance on russia: The role of double landlock geography in shaping geopolitics - Iswardhana, Muhammad Ridha (Trigin Publisher, 2026)
Uzbekistan is a landlocked country in Central Asia, is entirely surrounded by Kazakhstan, Kyrgyzstan, Afghanistan, and Turkmenistan, and lacks direct access to the sea. This geographical disadvantage, combined with its historical ties to the Soviet Union, presents significant economic and geopolitical challenges. Uzbekistan’s landlocked status limits its ability to engage in international trade, creating a reliance on neighboring countries, particularly Russia, for access to maritime routes. This dependence not only increases transportation costs but also complicates Uzbekistan’s ability to fully integrate into global markets. As a result, Uzbekistan faces constraints in its economic development and must navigate complex political relationships with regional powers. This research adopts a qualitative, descriptive-explanatory methodology, incorporating geopolitics theory to analyze Uzbekistan's landlocked status. The findings highlight the significant consequences of being a landlocked country, emphasizing the political, economic, and diplomatic implications of Uzbekistan's dependence on Russia for port access and trade infrastructure.